Management of the counterparty risk of an industrial enterprise - Ivanova, Z. (Економічний вісник Донбасу, 2017)
The modern industrial enterprise has extremely complicated economic relationships with its counterparties. The insecure and dynamic relationships and interrelations, on the one hand, and the multifaceted company mission and goals, on the other hand, undoubtedly generate the manifestation of the counterparty risk. This is a risk that can significantly influence the state and performance of an industrial structure, its competitiveness and market efficiency. The ability of the enterprise to develop and apply an adequate and reliable method of counterparty risk management becomes a vital factor for its normal functioning and future development. The purpose of this article is to pinpoint some of the specific peculiarities of the counterparty risk and to justify the opportunities of its management, which can then lead to limiting and reducing the unfavourable consequences and risk exposure of the industrial enterprise. Сучасне промислове підприємство має надзвичайно складні економічні відносини зі своїми контрагентами. З іншого боку, невизначені і динамічні відносини і взаємозв'язки, а також багатогранна місія і цілі компанії, безсумнівно, породжують прояв ризику контрагента. Це ризик, який може суттєво вплинути на стан і продуктивність його промислової структури, її конкурентоспроможність і ефективність на ринку. Здатність підприємства розробляти і застосовувати адекватний і надійний метод управління ризиками контрагента стає життєво важливим фактором його нормального функціонування і майбутнього розвитку. Мета цієї статті – виявити деякі специфічні особливості ризику контрагента та обґрунтувати можливості його управління, що може призвести до обмеження та зменшення несприятливих наслідків і схильності до ризику промислового підприємства. Современное промышленное предприятие имеет чрезвычайно сложные экономические отношения со своими контрагентами. С другой стороны, неопределенные и динамичные отношения и взаимосвязи, с одной стороны, и многогранная миссия и цели компании, несомненно, порождают проявление риска контрагента. Это риск, который может существенно повлиять на состояние и производительность его промышленной структуры, ее конкурентоспособность и эффективность на рынке. Способность предприятия разрабатывать и применять адекватный и надежный метод управления рисками контрагента становится жизненно важным фактором его нормального функционирования и будущего развития. Цель этой статьи – выявить некоторые специфические особенности риска контрагента и обосновать возможности его управления, что может привести к ограничению и уменьшению неблагоприятных последствий и подверженности риску промышленного предприятия.